Investigating Polish Students’ Research Competences: A Questionnaire Study - Kusiak-Pisowacka, Monika (2024)
The article reports on a questionnaire study which explored how sixty one students of English studies enrolled at a Polish university understood the concept of research and how they evaluated their own research skills in the context of their education. The findings revealed that all the students were aware of the importance of developing research competences. Although most of the respondents were willing to participate in research-oriented activities offered by university programs, there were students who did not approve of this form of teaching. The analysis of students’ answers provided valuable information that can be used in adjusting the teaching program to the students’ possibilities. The study points to the effectiveness of this kind of investigation in eliciting students’ perspectives on this important component of academic instruction.
Keywords: university education; research skills; discourse community; students as researchers